Studi Fenomenologi Interpretatif Tentang Upaya Pemerintah Daerah dalam Peningkatan Kesempatan Kerja Bagi Penyandang Disabilitas Melalui Program Pelatihan Ketenagakerjaan - Muhammad Syahru Ramadhan; Teza Yudha; Rachmat Ramdani (Yayasan Literasi Sains Indonesia, 2025)
This study aims to explore the meaning of local government actors' experiences in efforts to increase employment opportunities for people with disabilities through employment training programs. This study uses an interpretive phenomenological approach, so it will focus on how local government actors interpret their experiences, challenges, and results that arise in the implementation of employment training programs for people with disabilities. The data used in this study was collected through in-depth semi-structured interviews with key actors in the local government environment as well as analysis of policy documentation and employment training programs. The results show that despite the existence of a regulatory framework that supports the employment rights of persons with disabilities, its implementation still faces structural and cultural barriers. Some of these obstacles include low interest from the business world, limited inclusive training facilities, and a lack of direct involvement of persons with disabilities in program planning. However, there are also progressive local initiatives, such as training based on real labor market needs and collaboration with non-governmental organizations. This study recommends strengthening collaborative inclusive strategies and improving policy evaluation based on the direct experiences of implementing actors.